Pengaruh Brand Awareness, Promotion Mix Dan Word Of Mouth Terhadap Keputusan Pembelian Pada Rokok Djarum La Di Kota Malang - Dimas Saputro Legowo; Muhammad Mansur; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2023)
Abstract Djarum LA cigarettes are one of the many cigarette brand products issued by PT Djarum. The marketing carried out is of course supported by several factors on how consumers are able to decide on their purchase of Djarum LA cigarette products in Malang City. The purpose of this study was to determine and analyze the simultaneous and partial influence of brand awareness, promotion mix and word of mouth on consumer purchasing decisions on Djarum LA Cigarettes in Malang City. The population in this study were consumers of Djarum LA cigarettes in Malang City. Determining the number of samples using the Maholtra formula, and the results obtained were 80 respondents. The sampling method uses a non-probablity sampling technique with purposive sampling which uses a collection technique based on certain criteria. The results of the study show that brand awareness, promotion mix and word of mouth simultaneously and partially influence the purchasing decisions of consumers of Djarum LA cigarettes in Malang City. Keywords : Purchase Decision, Brand Awareness, Promotion Mix Word of Mouth.